Case Report: Successful surgical intervention for portal hypertension caused by primary hypoplasia of the portal vein in a dog - Shin, Joon-Ho; Han, Hyun-Jung (Frontiers in Veterinary Science, 2025)
An 11-year-old, 5-kg castrated male Miniature Poodle presented with persistent ascites lasting 3 weeks. A thorough physical examination, comprehensive blood tests, and diagnostic imaging (including radiography, ultrasonography, and computed tomography) revealed ascites, splenomegaly, hepatomegaly, and decreased portal vein velocity (5–6.6 cm/s), leading to a diagnosis of portal hypertension. Prehepatic and posthepatic causes were ruled out, and the patient was diagnosed with intrahepatic portal hypertension. Despite conservative management with diuretics and a sodium-restricted diet, severe ascites persisted. A surgical liver biopsy via exploratory laparotomy was performed to determine the specific cause of intrahepatic portal hypertension. Concurrently, splenectomy was carried out after identifying splenomegaly and congestion, which were likely associated with portal hypertension. Histological examination of the spleen revealed mild-to-moderate congestion and complex nodular hyperplasia, while liver examination confirmed a diagnosis of primary hypoplasia of the portal vein (PHPV). Postoperatively, the dog experienced a transient increase in ascites and complications such as anorexia, mild anemia, and hypoalbuminemia, all of which were managed with supportive care. From postoperative day 4, the ascites completely resolved, and the portal vein velocity normalized (17–18 cm/s). Four months post-surgery, the patient showed no further signs of ascites. This case report describes the diagnosis and successful management of PHPV-induced portal hypertension in a dog, highlighting the efficacy of splenectomy in resolving ascites and improving portal vein hemodynamics in cases of PHPV in dogs.